ANALYSIS OF FACTORS ASSOCIATED WITH SELF CARE IN POSTSTROKE PATIENTS AT THE ISLAMIC HOSPITAL CEMPAKA PUTIH, JAKARTA - Susanti, Ricka Ardila; Sofian, Yani; Rayasari, Fitrian; Azzam, Rohman; Astuti, Widya (Jurnal Keperawatan, 2025)
Stroke is the third highest level of disability in the world. The prevalence ofdisability in Indonesia is 13.88% (4,270 people) with dependency levelsincluding 36.33% independent, 33.25% mild dependency, 7.10% moderatedependency and 9.43% severe dependency. Basic Health Research in 2018showed that DKI Jakarta was in 11th place with the highest stroke prevalenceat 12.2%. This research aims to analyzed factors associated with self-care inpost-stroke patients at RSIJ Cempaka Putih. This research used a quantitativeresearch design using an analytical study with a cross sectional approach.The Bivariate results show that there is a relationship between independentvariables including age, gender, education, physical domain, emotionaldomain and social domain. Multivariate results show that the most dominantfactors related to self-care include the social domain, education and age. Thefactors most related to self-care in post-stroke patients in this study are thesocial domain, education and age. The findings suggest health workers to beable to carry out holistic assessments (bio, psycho, social and spiritual)including exploring sources of support for patients in carrying out self-care,carrying out therapeutic communication and providing innovative groupactivities that can be carried out in stroke clubs